PI3K/AKT/mTOR-dependent stabilization of oncogenic far-upstream element binding proteins in hepatocellular carcinoma cells - Samarin, Jana; Malz, Mona; Rössler, Stephanie; Singer, Stephan; Bissinger, Michaela; Dooley, Steven; Schirmacher, Peter; Breuhahn, Kai (Hepatology, 2016)
Transcription factors of the far-upstream element-binding protein (FBP) family represent cellular pathway hubs, and their overexpression in liver cancer (hepatocellular carcinoma [HCC]) stimulates tumor cell proliferation and correlates with poor prognosis. Here we determine the mode of oncogenic FBP overexpression in HCC cells. Using perturbation approaches (kinase inhibitors, small interfering RNAs) and a novel system for rapalog-dependent activation of AKT isoforms, we demonstrate that activity of the phosphatidylinositol-4,5-biphosphate 3-kinase/AKT pathway is involved in the enrichment of nuclear FBP1 and FBP2 in liver cancer cells. In human HCC tissues, phospho-AKT significantly correlates with nuclear FBP1/2 accumulation and expression of the proliferation marker KI67. Mechanistic target of rapamycin (mTOR) inhibition or blockade of its downstream effector eukaryotic translation initiation factor 4E activity equally reduced FBP1/2 concentrations. The mTORC1 inhibitor rapamycin diminishes FBP enrichment in liver tumors after hydrodynamic gene delivery of AKT plasmids. In addition, the multikinase inhibitor sorafenib significantly reduces FBP levels in HCC cells and in multidrug resistance 2-deficient mice that develop HCC due to severe inflammation. Both FBP1/2 messenger RNAs are highly stable, with FBP2 being more stable than FBP1. Importantly, inhibition of phosphatidylinositol-4,5-biphosphate 3-kinase/AKT/mTOR signaling significantly diminishes FBP1/2 protein stability in a caspase-3/-7-dependent manner. Conclusion: These data provide insight into a transcription-independent mechanism of FBP protein enrichment in liver cancer; further studies will have to show whether this previously unknown interaction between phosphatidylinositol-4,5-biphosphate 3-kinase/AKT/mTOR pathway activity and caspase-mediated FBP stabilization allows the establishment of interventional strategies in FBP-positive HCCs.